2015
DOI: 10.1038/srep10418
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Autism Spectrum Disorders: Does Sex Moderate the Pathway from Clinical Symptoms to Adaptive Behavior?

Abstract: We explored sex differences in diagnostic categories, clinical symptoms and adaptive behavior of persons with autism spectrum disorders, as well as sex-specific correlations of clinical and adaptive caracteristics. The study involved 108 patients (83 males, 6.73 ± 4.33 years old) diagnosed with autism spectrum disorders (ASD). Assessment included ADI-R and Vineland Adaptive Behavior Scale II. Males were more often diagnosed with typical autism. There were no sex differences in the autistic symptoms, while fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
(59 reference statements)
2
30
0
1
Order By: Relevance
“…Thus far, studies of very young children have failed to identify sex differences in ASD symptoms among affected individuals [60, 61]. Outside of ASD-specific traits, one such study did also observe higher scores in affected females on the Daily Living Skills Subscale of the Vineland Adaptive Behavior Scales (VABS) [61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, studies of very young children have failed to identify sex differences in ASD symptoms among affected individuals [60, 61]. Outside of ASD-specific traits, one such study did also observe higher scores in affected females on the Daily Living Skills Subscale of the Vineland Adaptive Behavior Scales (VABS) [61].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, studies of very young children have failed to identify sex differences in ASD symptoms among affected individuals [60, 61]. Outside of ASD-specific traits, one such study did also observe higher scores in affected females on the Daily Living Skills Subscale of the Vineland Adaptive Behavior Scales (VABS) [61]. Another study of male and female adults with ASD found no sex differences in retrospective reports of childhood autism traits, in keeping with the pattern above, but sex differences in social communication were apparent in adulthood [62].…”
Section: Introductionmentioning
confidence: 99%
“…They also score higher on the “Taste, Smell, and Touch Response and Use” section of the Childhood Autism Rating Scale than boys with high functioning autism (Kumazakia, Muramatsub et al 2015). Finally, they are less likely to be diagnosed with typical autism than their male counterparts (Mandic-Maravic, Pejovic-Milovancevic et al 2015). …”
Section: Sex Differences In Autistic Diagnosis and Phenotypementioning
confidence: 99%
“…According to the latest research, the prevalence of autism in children of 8 years of age is 1 in 68 (23.6 in 1000 boys and 5.3 in 1000 girls) (4). The prevalence of ASD is averagely four times higher in boys than in girls, which has been explored in several ways -using biological studies (5), but also exploring sex specific differences in clinical symptoms of ASD (6). Furthermore, recent analyses from 2008 indicate that the prevalence of autism has increased 23% since 2006 (7).…”
Section: Sažetakmentioning
confidence: 99%